Efforts to Improve Fine Motor Skills through Structured Finger-Painting Activities in Early Childhood Children - Fithriyah Kamilah; Didik Suryadi; Septi Fitriana (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Low fine motor skills in children include finger control, hand-eye coordination, accuracy in following patterns, and independence in completing activities. This study aims to optimize the fine motor skills of B2 group children at Kiddie Land Early Childhood Education Center through structured finger-painting activities. The research was conducted using Classroom Action Research, consisting of planning, action, observation, and reflection steps. The research subjects consisted of 10 children aged 5–6 years in group B2. The results indicate that structured finger-painting activities can gradually optimize children's fine motor skills. In the initial observation, only 20% of the children reached the “adequate” and “good” categories. After the action in Cycle I, this increased to 60%, and in Cycle II, it rose to 90%. These findings suggest that structured finger-painting activities provide effective stimulation for optimizing fine motor skill development in early childhood. In conclusion, structured finger painting effectively enhances children’s fine motor skills, as demonstrated by significant improvements from the initial observation to Cycle II. This study offers both practical and theoretical contributions to early childhood education in selecting effective strategies to stimulate fine motor development.